A review on body weight perception and its associated factors among adolescents in Malaysia and worldwide - Jamani, Nurjasmine Aida; Said, Abdul Hadi; Abd. Aziz, Karimah Hanim; Abd Rahman, Mohd Aizuddin (World Journal Of Pharmaceutical And Medical Research, 2019)
Body weight perception differs according to how the individual describe their body figure. Some may underestimate their weight while the other may overestimate it. Wrong body weight perception may lead to various complications. Those who underestimate their body weight may end up with complications such as obesity and obesity related morbidity. Meanwhile, those who overestimate their body weight may engage in unhealthy eating habit such as anorexia nervosa and bulimia. This is a major concern especially among adolescents in which they are in a crucial period of life and may not yet mature enough to make the best decision in particularly with regard to their health and health-related behavior. More importantly, several studies found psychological impact related to body weight perception. Depression and anxiety can be caused by the negative psychological effects of poor body image and distorted perception of body weight. Result from a study done among Chinese adolescents revealed that perceived overweight boys and girls were more likely to experience anxiety and depression as compared to those who perceived their body as normal and underweight. [1] A study in United States among high school students concluded that perceiving oneself as very underweight or very overweight was related with greater risk for suicidal attempts. [2] Therefore, this review aimed to discuss on the previous studies done investigating the prevalence and associated factors of body weight perception among adolescents in Malaysia, Asia and worldwide. It is hoped that this article will give us a better understanding regarding adolescent’s body weight perception and shall help us to plan future healthy lifestyle intervention necessary aiming for our adolescents’ population